2021
DOI: 10.14710/jil.19.1.21-28
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Fires and Its Environmental Conditions

Abstract: Today, many wetlands have been converted into agricultural, industrial, and residential areas. This conversion of land functions creates new problems for the environment and human, one of which is land fires. The results of land fires can also cause other problems that results in losses in various fields, such as human health, the economy, and other fields. The emergence of smog as a result of land fires can cause respiratory problems, disruption of the transportation system, conflicts between neighboring coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…East Kalimantan is one of the Provinces where forest and land fires are increase almost every year. This research uses an analytical descriptive method to identify the research area and collect secondary data [4,43]. Secondary data collected is hotspot data from 2012-2022 which was recorded from S-NPP VIIRS satellite imagery in East Kalimantan.…”
Section: Methodsmentioning
confidence: 99%
“…East Kalimantan is one of the Provinces where forest and land fires are increase almost every year. This research uses an analytical descriptive method to identify the research area and collect secondary data [4,43]. Secondary data collected is hotspot data from 2012-2022 which was recorded from S-NPP VIIRS satellite imagery in East Kalimantan.…”
Section: Methodsmentioning
confidence: 99%
“…Ogan Ilir is one of the regencies in South Sumatra with the most land fires every year. Data from Lestari et al (2021) show that there were 317 hotspots that occurred in 10 districts in Ogan Ilir in 2019. This number was the highest compared to the previous year.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics, natural factors that cause fires due to the accumulation of foliage or litter, wind, rock friction, and heat in the dry season trigger fires (Arisanty et al 2020). The study by Lestari et al (2021) conducted in the Ogan Ilir area showed that the most frequently burned areas were peaty soil (53%) and scrub vegetation (43%). Wetland fires, particularly in peat soils are very dangerous and difficult to detect especially if they occur in the dry season (Nurhayati et al 2020).…”
Section: Introductionmentioning
confidence: 99%